Innovation and Challenges of Smart Metrology in the Industry 4.0 Era - Zhao, Yubin (Transactions on Computer Science and Intelligent Systems Research, 2024)
Smart Metrology refer to a way of measure thing by advance technology, those technology include IOT, AI and Deep Learning. It’s not only just a way of measure thing, but also provide manufacturing some way to manage themselves, especially within the framework of Industry 4.0/5.0. in this article, we will talk about some cutting-edge technology and typical case, from there, we will learn and get some basic metrology data. Finally, the challenges and trends will be discussed including some influence.